The twist of a knife : a novel - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Hawthorne series, 2022)
"In New York Times bestselling author Anthony Horowitz's ingenious literary whodunit, Horowitz himself becomes the prime suspect in a murder investigation--and only one man can prove his innocence: his newly estranged partner in solving crime, Detective Daniel Hawthorne"--Dust jacket flap.